Screening Mental, Social, and Health Readiness Among Prospective Brides and Grooms - Zauhani Kusnul; Nugroho, Christianto; Herin Mawarti; Wiwik Afridah; Yuly Peristiowati (Journal Of Nursing Practice, 2026)
Background: Entering marriage is a crucial developmental phase, requiring thorough preparation to achieve the goals of marriage. The mental, social, and health readiness of prospective brides and grooms is crucial for the well-being of future generations. Purpose: The purpose of this study was to screen prospective brides and grooms for their mental, social, and health readiness. Methods: This observational study was conducted on 30 prospective brides and grooms in the Pare District Office of Religious Affairs (KUA) area, the samples take by with accidental sampling without inclusion and exclusion criteria. The variables included mental and social readiness, healthy lifestyle habits, blood pressure, and upper arm circumference for prospective brides and grooms. Results: The results showed that the prospective brides and grooms' mental and social readiness was relatively good. Regarding health readiness, two prospective brides had a low upper arm circumference (MUAC) and three prospective grooms had high blood pressure. Regarding smoking habits, the majority of the 15 prospective grooms, except for two, were smokers. Conclusion: The conclusion of this study are expected to provide important information in identifying issues in the health readiness of prospective brides and grooms that require strengthening.